Control quimico de malezas en policultivos con yuca (Manihot esculenta Crantz) - López M., J.; Leihner, D.E. (1980)
In view of the lack of information on the use of herbicides in polycultures including non-commercial crop species, 2 expt. were designed to identify herbicides and doses suitable for crop associations including cassava. A total of 6 products were tested single or in mixtures having been chosen for their selectivity of cassava, which was considered as basic crop. Besides cassava, other crops included in this study were maize, dry beans, cowpea, mung beans, groundnuts, Desmodium heterophyllum, and Crotalaria sp. Herbicides were identified with selectivities ranging from very specific to rather broad, oxifluorfen being the most specific (selective only to cassava and groundnuts) and linuron having the broadest range of selectivity (selective of at least 6 crops). Two mechanisms were studied simultaneously to reduce phytotoxicity to each crop and increase the no. of crops not affected by the herbicides:(1) the use of half doses of herbicides, and (2) preplanting application. While the application of half doses increased the selectivity of all herbicides, the preplanting application practice had this effect only with some of the testedproducts. The best combination showing selectivity of all crops, except D. heterophyllum, together with an efficient weed control was linuron + metolachlor at 0.25 + 1.0 kg a.i./ha in either pre or postplanting application. The results further indicate that chemical weed control in polycultures is feasible using low doses of herbicides with a wide range of selectivity. (AS)